The structure and procedure of economic calculations for the organization of remuneration in crisis enterprises - A. R. Bril; O. V. Kalinina; A. A. Sedyakina; S. V. Kalmykova (Омский научный вестник: Серия "Общество. История. Современность")
Planning and organization of remuneration, staff incentives for the withdrawal of a company from a crisis situation requires in some cases significant financial resources. This situation occurs in cases where, in order to preserve the most efficient employees of the enterprise, it becomes necessary to use special methods of motivation and remuneration. To work out the various options for the plan and effectively address these issues, reliable information is needed on the economic and organizational capabilities of the enterprise, the level of risks and the state of the market. In order to prepare such information, the article proposes a settlement system and a decision-making procedure based on the separation of the principles of external and internal analysis, the development of the company’s regulatory budget and a business plan for overcoming the crisis